IN THE SHADOWS OF MODERNITY: Performing and Preserving the Bukoba Tradition Among Malay Society in Riau, Indonesia - Ansor, Muhammad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The following article explores the ways in which Bakoba oral literary cultures in Malay Riau, Indonesia, are being kept alive through performance. The author argues that the oral literary tradition that is an integral component of the cultural identity of the Malay people of Riau is in threat of losing out due to the pressures of modernity and the efforts that have been made to regenerate the tradition. In-depth interviews, observations, and documentation studies were carried out in Rokan Hulu, which is located in the province of Riau, as part of this study, which employs a qualitative approach to data gathering methodologies. The findings of the study highlight the complicated features of the Bukoba transmission process as well as the difficulties that are encountered by dealers. The research also revealed that the rapid growth of technology and modernity led to a shrinking of the arena for traders to display Bukoba oral traditions in public areas. This resulted in a decrease in the number of public venues where these traditions were displayed. In the end, the writing arrived at the conclusion that the presence of the state was required in order to revitalise the oral literary heritage of the Malay Riau community in an effort to confront extinction. This conclusion was reached at the end of the writing.